Induction of somatic embryogenesis and plant regeneration of sugarcane cv. RB925345 from somatic embryos - Almeida, Rodrigo de Oliveira; Silva, Sérgio Delmar dos Anjos e; Dutra, Leonardo Ferreira (Scientia Agraria Paranaensis, 2018)
The aim of this study was to establish a protocol for induction of somatic embryogenesis and regeneration of somatic embryos of sugarcane (cultivar RB925345). Best results was obtained using concentration of 13.5 µM of 2,4-dichlorophenoxyacetic acid, 45 days of incubation on induction medium, one subculture and 15 days of incubation on regeneration medium, providing 47.5% of embryogenic calli and 38.9% of plants regenerated. Adjustments are necessary to this protocol to improve the embryogenic calli production rate and regeneration of somatic embryos.